Faecal Calprotectin for the Diagnosis of Bowel Inflammation in Patients With Rheumatological Diseases: A Systematic Review. (20th December 2019) - Fauny, Marine; D'Amico, Ferdinando; Bonovas, Stefanos; Netter, Patrick; Danese, Silvio; Loeuille, Damien; Peyrin-Biroulet, Laurent
Abstract: Background and Aims: Endoscopic and histological gut inflammation are present in half of patients with ankylosing spondylitis [AS] or spondyloarthritis [SpA]. We performed a systematic literature review on the use of faecal calprotectin [FC] in patients with rheumatic diseases. Methods: Searches of the PubMed, Web of Science, and Cochrane Library databases were performed up to September 2019 to identify all studies including adult patients with confirmed diagnosis of SpA or AS. Results: Seven studies met the inclusion criteria: six prospective observational studies and one retrospective observational study. Study populations consisted of SpA patients in four studies and AS patients in three studies. In six studies, an ELISA test was used for FC levels and in one case, a semi-quantitative assay was adopted. In all included studies, patients with SpA or AS had elevated FC levels, ranging from 21.2% to 70.7% of patients. In six studies, patients with increased FC levels had macroscopic mucosal inflammation, ranging from 11% to 80% of cases. Four studies highlighted the presence of microscopic alterations in patients with high FC levels, ranging from 41.7% to 100% of patients. An FC cut-off level predicting the inflammatory bowel disease [IBD] occurrence was found in two studies: 266 mg/kg and 132 mg/kg, with sensitivity and specificity of 100%, 78.7% and 66.7%, 76.9%, respectively. Conclusions: Faecal calprotectin is a useful and non-invasive marker to predict IBD in patients with SpA or AS. Gut histological and macroscopic mucosal inflammation were found in up to 100% and 80% of rheumatological patients with increased FC levels.